The impact of interpersonal communication on employee performance during work from home - Nurul Rezky Amalia; Sharmila Karuppaiah; Zainudin Hassan; Andi Anto Patak (International Journal of Humanities and Innovation (IJHI), 2023)
Interpersonal communication is a process of exchanging information, ideas, feelings, and opinion that two or more people carry out through verbal or non-verbal. This study aims to find out how far interpersonal communication impacts employee performance during work from home. In this research, six people were selected as research objects using purposive sampling. A semi-structured interview was conducted, and a list of questions was developed. Analysis of the research data using thematic analysis. The results of this study indicate the extent to which the impact of interpersonal communication while working at home, 1) good relations are established between employees, 2) greater employee involvement, and 3) increased teamwork. According to the study's findings, enhanced teamwork, higher employee involvement, and strong relationships among co-workers indicate how much interpersonal communication affects work-from-home employees. Because of the effectiveness of their communication, their performance is affected, and performance outcomes improve with improved staff communication.